One step access to oxindole-based β-lactams through Ugi four-center three-component reaction. Issue 61 (11th October 2018) - Rainoldi, Giulia; Lesma, Giordano; Picozzi, Claudia; Lo Presti, Leonardo; Silvani, Alessandra
Abstract : A multicomponent Ugi reaction involving isatin, isocyanide and β-amino acid components has been developed. Abstract : A multicomponent Ugi reaction involving isatin, isocyanide and β-amino acid components has been developed. The reactions proceeded smoothly to give β-lactam-containing 3, 3-disubstituted oxindoles in only one step and generally high yields. When chiral, non racemic, β-amino acids were used, products were obtained as enantiomerically pure β-lactams diastereoisomers, whose relative stereochemistry was determined by X-ray analysis. For one compound, a weak antibacterial activity has been preliminarily highlighted.